Environmental justice in South Africa: the dilemma of informal settlement residents - Ruhiiga, T. M.; Kekana, H. N.,; Ndou ·, N. N. (GeoJournal. https://doi.org/10.1007/s10708-022-10808-z, 2023)
The concept of environmental justice is well established in the literature; however, schol- ars still battle to agree on what it really means. This concept has become more relevant to the studies of informal settlements amongst others. The location and environmental variables in informal settlements suggests a variety of injustices that comes with loca- tion, limited access to water, poor or lack of sanita- tion, challenges with transport availability, accessibil- ity, affordability, and lack of other social amenities. These and many other socio-economic needs forms part of the value chain of environmental justice debates across the world. This paper deals with envi- ronmental justice in the informal settlements of Kos- mos, in the Madibeng Local Municipality, Bojanala Region in the North-West Province of South Africa.The paper highlights some of the environmental chal- lenges faced by the informal settlement residents such as pollution, waste management (landfill sites, waste collection) sanitation and water provision. The paper explores how the Kosmos informal settlement com- munity has been excluded from decision making pro- cesses regarding their own environment and consid- ers the levels of environmental injustices commonly associated with this kind of practice.